AN EFFICIENT AND SECURED NON BLIND WATERMARKING SCHEME FOR COLOR IMAGES USING DWT AND ARNOLD TRANSFORM - Dharwadkar, Nagaraj V.; Amberker, B. B. (International Journal of Computing, 2010)
In the early days, encryption and access control techniques are used to protect the ownership of image. Recently, the watermarking schemes are utilized to define the copyright of image. Digital watermarking is a concept of embedding a special security pattern into cover image. It has recently become important in various application areas of image processing. In this paper we present a new invisible, robust, non blind frequency domain watermarking scheme. This scheme embeds the monochrome (logo) watermark into the high and middle HL, LH, HH frequency bands of Arnold transformed luminance channel of the color image. The security of scheme is improved by scrambling the luminance channel of the color image using Arnold transform. In order to increase the detection speed and efficiency of algorithm, the location of modified high and middle frequency components are stored into key array. Use of this key array improves the speed of the extraction algorithm. The experimental results show that the watermark is robust against different types of attacks like image cropping, image filtering, image Compression, image blurring, and Image transformations. Further, the results of the proposed scheme are analyzed on the set of images.